Are sex and history of pruritic skin conditions factors which affect the phenomenon of visually evoked itch? An exploratory study. Issue 3 (December 2017) - Lloyd, Donna M.; Dodd, Rebecca; Higgins, Caroline; Burke, Melanie R.; McGlone, Francis
Abstract : Introduction: We have previously shown that sensations of itch and the scratch response can be evoked using itch-related images. However, we did not determine whether individual differences in a person's experience of itch could moderate this effect. This exploratory study aimed to determine whether sex or a history of pruritic skin conditions (PSCs) could influence the effects of visually evoked itch and scratch. Methods: Forty-one participants (19 males; 16 with a history of PSCs) viewed static images that could either be itch or nonitch related. These were further separated by picture type: "skin contact" (ants crawling on the hand vs. a butterfly on the finger); "skin response" (scratching an insect bite vs. washing the hands); "skin condition" (psoriasis vs. freckles) or "context only" (insects vs. birds). Images were rated using a 10-point scale by answering: "How itchy do you feel?" (Self-rating) and "How itchy do you think the person in the picture feels?" (Other-rating). Frequency and location of scratching was also recorded. Results: The highest itch scores were to itch-related skin contact pictures. Females gave higher itch ratings than males, and people with a history of PSCs gave higher itch ratings when viewing images of people scratching. There was no correlation between itch ratings and scratch response, and no relationship between body site viewed and location of scratching. Discussion: There is a heightened response to itch-related cues in females and those with PSCs, indicating a more centrally mediated pathway bringing subconscious itch sensations into conscious awareness in these populations. These findings could influence personalized treatment interventions aimed at reducing awareness of itch sensations in susceptible individuals.